2016
DOI: 10.1371/journal.pone.0165713
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-Associated, Antibiotic-Resistant Staphylococcus aureus Nasal Carriage and Recent Skin and Soft Tissue Infection among Industrial Hog Operation Workers

Abstract: Swine production work is a risk factor for nasal carriage of livestock-associated (LA-) Staphylococcus aureus and also for skin and soft tissue infection (SSTI). However, whether LA-S. aureus nasal carriage is associated with increased risk of SSTI remains unclear. We aimed to examine S. aureus nasal carriage and recent (≤3 months prior to enrollment) SSTI symptoms among industrial hog operation (IHO) workers and their household contacts. IHO workers and their household contacts provided a nasal swab and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…Numerous studies, examining the transmission of antimicrobial resistant bacteria from animal to humans, reported the high prevalence rate of antimicrobial resistant bacteria among individuals that have a direct contact with animals, specifically farm workers [61,62] and veterinarians [63]. Among the first authors, Levy and colleagues [64] reported a direct transmission of multidrug resistant E. coli from animals to animals and also from animals to humans.…”
Section: Zoonotic Transmission Of Antimicrobial Resistance To Humansmentioning
confidence: 99%
“…Numerous studies, examining the transmission of antimicrobial resistant bacteria from animal to humans, reported the high prevalence rate of antimicrobial resistant bacteria among individuals that have a direct contact with animals, specifically farm workers [61,62] and veterinarians [63]. Among the first authors, Levy and colleagues [64] reported a direct transmission of multidrug resistant E. coli from animals to animals and also from animals to humans.…”
Section: Zoonotic Transmission Of Antimicrobial Resistance To Humansmentioning
confidence: 99%
“…Most projects led to scientific discoveries and innovations. CS projects resulted in new plant varieties for organic farming (Lyon et al 2018); greater understanding of pollinator health (Bloom and Crowder 2020); evidence of linkage between antibiotic-resistant bacteria and livestock worker health (Guidry et al 2018;Hatcher et al 2017aHatcher et al , 2017bNadimpalli et al 2015Nadimpalli et al , 2016Rhodes et al 2020;Rinsky et al 2013); and documentation of pesticide drift into homes and schools (Harrison 2011(Harrison , 2017Marquez and Schafer 2017). Some projects directly helped community members to document contamination from oil sands development (Baker 2016;Baker and Fort Mackay Berry Group 2019) and from an oil spill (Simon-Friedt et al 2016;Wickliffe et al 2018;Wilson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent drug-resistant organisms that are met in the health care settings are methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae, multidrugresistant Pseudomonas aeruginosa, Enterococcus faecium, Klebsiella pneumoniae, and Acinetobacter baumannii [6][7][8][9] . These pathogens are commonly known to be ESKAPE pathogens, and these are majorly accountable for nosocomial infections and are skilled in "escaping" the antimicrobial agent's action 10,11 .…”
Section: Introductionmentioning
confidence: 99%